A Podcasts Utilization Through Instagram Media in Increasing The Motivation of The Millennial Generation in The Quarter Life Crisis Phase - Dewi , Bekti Nirmala; Apriliani, Putri Naya; Rahmawati, Raida Ananda; Dharma, Grace Widya; Rachmanissa , Tiara; Autentica , Veny; Yodsuban, Pairin (Inovasi Lokal, 2023)
Quarter life crisis is a feeling that arises when an individual reaches a quarter of a century (towards 25 years), where there is a feeling of fear about the continuation of life in the future, including career matters, relationships and social life. A person in this crisis experiences a loss of motivation to live, feels like a failure, loses self-confidence and meaning in life, and even withdraws from social interactions. Delivering motivation to the millennial generation through podcast media aims to find out how behavior changes and ways to adapt in phases quarter life crisis. The research method used is a descriptive qualitative approach, which starts with data collection through interviews with sources via an application chat audio Whatsapp on October 11 2023, then uploaded the podcast on the Instagram page and conducted a survey of podcast listeners through likes and comments on the Instagram post where the podcast was uploaded. Through this research, the results were obtained from a podcast with the title “How To Deal With Quarter Life Crisis?” This has received a lot of attention from Instagram users and can be a solution to increase the motivation of the millennial generation in facing this phase quarter life crisis